FISHERIES ASSOCIATED WITH MANGROVE ECOSYSTEM IN INDONESIA: A View from a Mangrove Ecologist - SUKRISTIJONO SUKARDJO (SEAMEO BIOTROP, 2004)
Blessed with mangrove area of some 9.6 million ha in extent, Indonesia represents an important country with fishery resources being a source of food and nutrients. The fishery resources utilized by man, such as fishes, crustaceans and mollusks that are found in the mangrove ecosystem/swamp area arc enormous. There is a range of species caught in the mangrove and surrounding areas with over 70 species. However, commercially valued species are limited to a few such as rabbit fish, snapper, grouper, marline catfish, fringe-scale sardine, and anchovy. Leaf detritus from mangroves contribute a major energy input into fisheries. But information about the study on the relationship between fishery species and mangroves, ecologically and biologically, arc scanty. The mangrove is a physiographic unit, the principal components of which arc organisms. Therefore, the problems are predominantly of a biological nature (e.g., mangroves - fishery relationship). Positive correlation between the mangrove area and penaeid shrimp catch found in Indonesia, the Philippines, Australia and Mexico. Finally, the most important part of the variance of the MSY (Maximum Sustainable Yield) of penaieds (53% of the variance) could be explained by a combination of area of mangrove habitats and latitude. KeywordsÂ :Â Â Indonesia/Mangrove/Ecosystem/Fisheries/Ecology/Coastal areas/Fishes/Molluscans/ Crustaceans.